Um réquiem para Diadorim (Nonada : dois dedos de prosa-poética sobre o amor e outras bossas no Grande sertão : veredas) - Lourenço, Wander (2006)
This intitled research Um réquiem para Diadorim (Nonada dois dedos prosapoética sobre o Amor e outras bossas no Grande sertão: veredas) , will be considered to argue the evolution of the modern narrative, in regards to thematic of Love and its sources in the literary composition of the authorship of Guimarães Rosa. This paper will be divided at three moments that will bear to investigate, through the bias of the reminiscences of the gunman-narrator Riobaldo Tatarana or Urutu-Branco, the trajectory of the fictional prose to the passions and referring reflections to the passage of the plot-passage of the romance published in 1956. Part I, intitled Um trípico Amoroso - Diadorim, Octacília and Nhorinhá , will present the analysis of this triangle formed for the androgynous figure of Reinaldo, the prostitute 'namorã' Nhorinhá and for Otacília, `abençoável' sinhazinha casadoira . In Part II, called Diadorim - a invenção do Amor? in the scope of the narrative nonsenses and divagations, the mystery or enigma of this emblematic be-sign and hermaphrodite, Reinaldo/Maria Deodorina of the Faith Bettencourt Marins. Finally, in Part III, under the heading of Reinaldo a inversão do outro , will be approached with more emphasis, from the positioning of the critical tradition, the intricate tram and its tragic outcome, based in multiple interpretations on the sexuality of the son of Joca Ramiro. Considering that, in this ambiguous space of the sertões of the rosianos generalities if it would restore an emblematic and fancy story of Love, fits to point out that the mentioned divisions of the hermeneutics in question constantly will be interpenetrated, in the proposal of if elucidating how much possible, in the meaning of the artistic word, from the archaic speech of the hero with reumatismos , the trajectory of the literary composition Grande Sertão: trails, for on rivers, valleys, crossroads, vilarejos and, over all, for on the incursion for the spirit of the creation in its extraordinaire condition human being.